2021
DOI: 10.1186/s12876-021-02057-0
|View full text |Cite
|
Sign up to set email alerts
|

8DEstablishment and validation of a hypoxia-related signature predicting prognosis in hepatocellular carcinoma

Abstract: Background Hypoxia plays a crucial role in immunotherapy of hepatocellular carcinoma (HCC) by changing the tumor microenvironment. Until now the association between hypoxia genes and prognosis of HCC remains obscure. We attempt to construct a hypoxia model to predict the prognosis in HCC. Results We screened out 3 hypoxia genes (ENO1, UGP2, TPI1) to make the model, which can predict prognosis in HCC. And this model emerges as an independent progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The outcomes of HCC patients are closely correlated to the expression of a few genes in the tumor tissue, tumor stage, tumor size, serum indicators, and liver function. To predict the prognosis of HCC patients, several studies have concentrated on the possible relevance of gene signatures based on aberrant messenger ribonucleic acid (29)(30)(31). Using data from TCGA as the training set and data from ICGC as the validation set, we combined the gene expression data for HCC in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of HCC patients are closely correlated to the expression of a few genes in the tumor tissue, tumor stage, tumor size, serum indicators, and liver function. To predict the prognosis of HCC patients, several studies have concentrated on the possible relevance of gene signatures based on aberrant messenger ribonucleic acid (29)(30)(31). Using data from TCGA as the training set and data from ICGC as the validation set, we combined the gene expression data for HCC in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The construction of a prognostic model based on the expression of multiple genes in PCA is more meaningful for predicting the prognosis of PCA patients. Previous studies have explored the predictive role of hypoxia-related prognostic models in the prognosis of hepatocellular carcinoma ( 13 ), glioma ( 14 ), and breast cancer ( 15 ) patients. This study aimed to develop a hypoxia-related prognostic model to predict the prognosis of PCA patients and assess the TME.…”
Section: Introductionmentioning
confidence: 99%
“…Dao et al identified and validated a reliable hypoxia-related survival score in IDH-mutant glioma stem cells based on five HRGs (LYVE1, FAM162A, WNT6, OTP, and PLOD), which was significantly related to the survival of patients with glioma [ 11 ]. Cai et al constructed and validated a prognostic model for hepatocellular carcinoma (HCC) composed of three hypoxia genes (ENO1, UGP2, and TPI1), which was shown to be effective for the prognosis of HCC patients [ 12 ]. Although previous study indicated that downregulated hypoxia transcriptome in vitro was closely related to the depressed prognosis in BC [ 13 ], the prognostic values of HRGs in BC was still unclear and attract us to further study on it.…”
Section: Introductionmentioning
confidence: 99%